STARS WITH HA EMISSION IN GALACTIC LONGITUDES 59 TO 90 - GONZALEZ, G; GONZALEZ, G (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1960)
A catalogue of 212 new early type stars with Halpha in emission classified between l= 59° and 90° is presented.
BOL OBS TONAN TACUB
Keywords: STARS, EMISSION, GALACTIC, LONGITUDES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; GALAXIAS